2021
DOI: 10.30739/dej.v1i1.1034
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Students� Perceptions in Learning Speaking through Picture Media

Abstract: The general aims in this research are to find out the students perceptions in learning speaking through picture media at the eleventh grade students of MA Roudlotul Muta�alimin in academic year 2019/2020. Furthermore, the aims can particularly be formulated to know what students perceptions in learning speaking through picture media. This research was categorized as survey research with the descriptive quantitative approach. The subject of this research is the eleventh grade students of MA Roudlotul Muta�alimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These strategies are in fact popular and widely used by teachers around the world. Ahmada and Munawaroh (2022) and Rochman ( 2014), for instance, suggested that roleplay is effective to increase students' motivation to participate in speaking classes. Besides, referring to Zuhriyah (2017) and Zaid and Sarjiyati (2019), storytelling is also proven to be effective in improving students' comprehension, fluency, vocabulary, grammar, and pronunciation.…”
Section: The Use Of English In Classroommentioning
confidence: 99%
“…These strategies are in fact popular and widely used by teachers around the world. Ahmada and Munawaroh (2022) and Rochman ( 2014), for instance, suggested that roleplay is effective to increase students' motivation to participate in speaking classes. Besides, referring to Zuhriyah (2017) and Zaid and Sarjiyati (2019), storytelling is also proven to be effective in improving students' comprehension, fluency, vocabulary, grammar, and pronunciation.…”
Section: The Use Of English In Classroommentioning
confidence: 99%